Combating fake news online: exploring Australian co-regulatory framework for Malaysia - Daud, Mahyuddin (2019)
It has been witnessed that the booming of digital technologies had stimulated positive impact towards usage of social media. Although this has been fruitful to increase Internet penetration, social media has turned into a nesting ground to spread fake news that tarnishes national reputation. This research analyses legal framework on regulation of fake news online in Malaysia and selected jurisdictions. Three recent initiatives were highlighted, namely (1) introduction of a website – ‘Sebenarnya.my’ designed to verify authenticity of news; (2) emplacing liability on WhatsApp group administrator to monitor false content; and (3) enactment of the Anti-Fake News Act 2018. Through qualitative method, the research records key observations on how popular social media platforms designs necessary countermeasures to combat fake news and how far such technical initiatives correspond with existing legal frameworks. As part of recommendation, Australian co-regulation’s classification and filtering measures could be of reference to Malaysia in its effort to combat fake news online. In gearing towards a healthier, dynamic and progressive digital society, proactive measures taken must be balanced with constitutional right to freedom of expression within boundaries set by the laws.